A Analisis Akuntansi Perpajakan PPh 22 atas Pengadaan Barang Pada Diskominfo Provinsi Jawa Barat - Lisda Febrianti; Ardiansyah (LPPM STIE PPI, 2024)
Introduction/Main Objectives: To determine whether the calculation, deposit and reporting of PPh 22 at the West Java Provincial Communication and Information Office are in accordance with the Regulation of the Minister of Finance No. 231/PMK.03/2019. Background Problems: Government agencies in their activities to realize the budget are not free from transactions that are subject to tax. Novelty: Conducting tests on different units of analysis related to the Regulation of the Minister of Finance No. 231/PMK.03/2019. Research Methods: Using a qualitative method with a descriptive analysis method in the form of case studies and literature studies. Findings/Results: That the deposit of PPh 22 is on time and in accordance with applicable tax regulations, it's just that there are still partners who do not have a NPWP so that the PPh 22 rate used is higher and the reporting of PPh 22 is still not on time. Conclusion: Strengthening internal policies related to tax management must be carried out by establishing clear and detailed standard operating procedures and the importance of effective and integrated management in handling tax obligations.